The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pol.20210311
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and applications of stimuli‐responsive micro/nanopillar arrays

Abstract: The functional surface features of living creatures are driven by the complex morphology of periodically arranged micro/nanoscale structures. Various fabrication processes have been devised mimic the performance of natural features; these methods morph hierarchical and multi-leveled pillar arrays, such as top-down, bottom-up, and a hybrid of top-down and bottom-up processes.Different methodologies are employed depending on the materials, such as polymeric composites, metal oxides, metals, and carbon nanotubes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 179 publications
0
17
0
Order By: Relevance
“…We also observed that the assembly of arrays occurred despite small contact areas among pillar tops, unlike in the case of capillary-collapsed nanopillar arrays . The polymeric solutes are localized at the interspace of self-assembled micropillars. The original upright states of the micropillars were retrieved with regular spacings by simply rinsing out the water-soluble polymers. Therefore, micropillar arrays can be subjected to magnetic actuation or the evaporation of a polymeric solution for reversible chirality selection or capillary-assisted self-assembly.…”
Section: Resultsmentioning
confidence: 79%
“…We also observed that the assembly of arrays occurred despite small contact areas among pillar tops, unlike in the case of capillary-collapsed nanopillar arrays . The polymeric solutes are localized at the interspace of self-assembled micropillars. The original upright states of the micropillars were retrieved with regular spacings by simply rinsing out the water-soluble polymers. Therefore, micropillar arrays can be subjected to magnetic actuation or the evaporation of a polymeric solution for reversible chirality selection or capillary-assisted self-assembly.…”
Section: Resultsmentioning
confidence: 79%
“…These well-defined nanostructures with high freedom of structural designability could result in some unique properties. Furthermore, external stimuli (e.g., capillary force, light, magnetic field, and heat) will further adjust these properties in a dynamic way 7 . Such promising features should be in favor of device utilization.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the compelling requirement of device miniaturization, synthesis of nanoscopic structures and their macroscopic integration into a large-scale array are fundamental to modern and future devices in the fields of optics 1 , electronics 2 , telecommunication 3 , biology 4 , energy conversion/storage 5 , 6 , and stimuli-responsive materials 7 , etc. It is known that nanostructures are subject to physical and chemical property variation as a function of their geometry and composition; 8 and arrayed assemblies of these nanostructures exhibit collective behaviors of their responses in terms of coupling in the same set and synergy between different sets 9 , 10 , .…”
Section: Introductionmentioning
confidence: 99%
“…An example of small scale devices is micro-and nanopillars assembled into arrays on the flat substrates [2]. Areas of applications of small-scale pillar arrays include e.g.…”
Section: Introductionmentioning
confidence: 99%